ESP Course Design for Indonesian Hotel Industry: Need Analysis - Yuyud Tri Guntoro (Masters in English Education, The Directory of Postgraduate Program,Universitas Muhammadiyah Malang, 2021)
English for Specific Purpose (ESP) runs to equip learners’ English language for their future needs in tertiary education. In the hotel industry, the laborers’ English capabilities are crucial as their duties deal with foreign guests. However, hotel employees’ English language inability was found in a small case. Thus, the ESP argues able to advance labor’s English language skills. This research aims to identify staff’s English needs in the front-desk department by identifying labors’ lacks, wants, and necessities. Furthermore, this paper also seeks the expected ESP course. The data were collected toward three staff and a hotel manager by using the qualitative method. Additionally, interview and participant observation has established in Kapal Garden Hotel, Indonesia. The result are 1.) Speaking and listening are primary skills for a front desk job. It is in line with work necessities that front desk staff’s duties are to communicate with foreign guests. The ESP course is expected to lead the students to pronounce vocabulary in hotels, respond to the conversation in the check-in and check-out situation, explain hotel facilities, direct the guest to a certain place, and understand the various foreign accents. 2.) The staff expects flexible teaching for ESP course design.